Volunteering as a Way of Taking Responsibility for the Sustainability of Social Economy Enterprises - Tudor, Ion; Predețeanu, Daniela Ileana; Picu, Cătălina; State, Cristina (European Journal of Sustainable Development, 2020)
Our study is about the perception of people towards volunteering, in order to propose solutions to improve the management for the sustainability of social economy enterprises. The question we want to answer in our paper is about the availability for participation in voluntary activities to ensure the sustainability of social economy enterprise. This question became the main objective of our study. To answer this question we conducted a survey based on a questionnaire in a micro-community from the Centre Region of Romania. Combining the quantitative and qualitative methods, thus ensuring the in-depth interpretation of the study results, the work hypotheses were tested with the IBM Statistics and AtlasTi applications. The results of our study confirm that the subjects surveyed are willing to take the responsibility of engaging in volunteering for the benefit of individuals or the community, thereby contributing to the creation of tangible economic and social values for the community. Finally we conclude that involving individuals in volunteering activities can be an valuable piece of information for the managers of social enterprises when it comes to taking the adequate strategic decisions, so as to obtain a competitive advantage that can be materialized in the utility of the work, the personal satisfaction as a result of work done, the integration into community etc. Keywords: improving management, communities, social economy enterprise, solidarity, volunteering